Optimization of phenol adsorption from synthetic wastewater by synthesized BiFeO3 perovskite material, using split-plot central composite design - Garba, Zaharaddeen Nasiru (2023)
X-ray diffractometer (XRD) The detected peaks in the XRD patterns were identified as rhombohedra perovskite structure of BiFeO3 with space group R-3 m and lattice parameters a = b = c = 3.9520 (Å).